How important is perception-action coupling in the tennis serve? - Giblin, G.; Whiteside, D.; Reid, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to examine how removing visual feedback affects ball and racket kinematics in the tennis serve. A 10-camera 500 Hz VICON MX motion analysis system recorded the service actions of 8 elite junior players as they performed three serves with eyes open and three serves with eyes closed. Removal of vision resulted in considerable differences in both racket and ball kinematics, and the interaction between the two. The results highlight that the service action is not pre-programmed, and that visual feedback is critical to the temporospatial regulation of the service action. These findings suggest that coaches need to be aware of the implications of removing perception-action couplings, and ensure that the drills that they prescribe represent the action being trained.